Qardhul Hasan as a proposed tool for social financing through temporary cash waqf and zakah: a maqasid approach - Ghalia, Bouhedda; Subhani, Zulqernain Haider (2022)
This research article aims to study the possibility of actualizing temporary cash Waqf and Zakah in contemporary world as they constitute the basin pillars of social financing in Islamic financial and economic system, and they have a very important role in achieving higher intents of Shariah like justice, social cooperation, and economic welfare. The problem of the research lies in the differences of opinions of scholars regarding permissibility of applying Qardhul Hasan on Zakah and this article attempts to employ Maqasid approach to give the preference among those views as well as delineating the rules and proposing suitable tools for it. Similarly, it again taking Maqasid approach propose application of Qardhul Hasan on temporary cash Waqf. The study is carried out considering the contemporary Islamic banks in general and suggest for actual application in Malaysian context. Content analysis and comparative analysis methods have been used to carry out the research. The research concludes that applying Qardhul Hasan through temporary cash Waqf and Zakah for social financing is permissible in the light of Maqasid-e-Shariah.